Pendidikan Islam Multikulturalisme sebagai Solusi Permasalahan Keberagaman Agama di Lingkungan Pendidikan Indonesia - Hermawati, Adetiyah Syahputri; Anantia, Tasya Dewi; Deistyarini, Vidya Nendar; Purwanda, Indah; Dalimunthe, Rohimah (ALSYS, 2022)
Development in Indonesia follow development in every age/technology that exists, education in Indonesia has a stage in every education, the first stage of paud school, primary school, junior high school, high school and university college. In each aducation learners have a choice in their recpevtive fields. But each school has it own appeal in attactring learners to joint the education, but education in Indonesia is stil a lot of shortcomings especially in the form of educating learners to a higher level, educate learners in learning until graduation, educating learners in a fast association as it is today and there is still much to be improved in the form of education today. In edication also requires decent facilities and meets the needs of learners, facilities in the school, in the classroom an the school invironment must be able to be met with their respevtive needs. In education must be able to provide motivation to learners to help in building the spirit of learners.